2012
DOI: 10.1002/aur.1251
|View full text |Cite
|
Sign up to set email alerts
|

The Expanding Role of MBD Genes in Autism: Identification of a MECP2 Duplication and Novel Alterations in MBD5, MBD6, and SETDB1

Abstract: The methyl-CpG-binding domain (MBD) gene family was first linked to autism over a decade ago when Rett syndrome, which falls under the umbrella of autism spectrum disorders (ASDs), was revealed to be predominantly caused by MECP2 mutations. Since that time, MECP2 alterations have been recognized in idiopathic ASD patients by us and others. Individuals with deletions across the MBD5 gene also present with ASDs, impaired speech, intellectual difficulties, repetitive behaviors, and epilepsy. These findings sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 75 publications
2
62
0
Order By: Relevance
“…18 MBD5 variants MBD5-specific variants have been identified in a cohort of autism cases that also exhibit the phenotype of 2q23.1 deletion syndrome, including ID, severe speech impairment, seizures, and autistic-like behavioral problems (see Supplementary Table 1 for list of published MBD5 variants likely to affect function, GenBank accession numbers: NM_018328.4, and NP_060798.2). 2,7,15,[19][20][21][22] Variants were submitted to http://www.ncbi.nlm.nih.gov/clinvar/?term = MBD5[gene]). The identification of mutations in MBD5 in individuals with significantly overlapping features verified that MBD5 was the critical gene responsible for the core features of 2q23.1 deletion syndrome.…”
Section: Mbd5-associated Neurodevelopmental Disorder Sv Mullegama Andmentioning
confidence: 99%
“…18 MBD5 variants MBD5-specific variants have been identified in a cohort of autism cases that also exhibit the phenotype of 2q23.1 deletion syndrome, including ID, severe speech impairment, seizures, and autistic-like behavioral problems (see Supplementary Table 1 for list of published MBD5 variants likely to affect function, GenBank accession numbers: NM_018328.4, and NP_060798.2). 2,7,15,[19][20][21][22] Variants were submitted to http://www.ncbi.nlm.nih.gov/clinvar/?term = MBD5[gene]). The identification of mutations in MBD5 in individuals with significantly overlapping features verified that MBD5 was the critical gene responsible for the core features of 2q23.1 deletion syndrome.…”
Section: Mbd5-associated Neurodevelopmental Disorder Sv Mullegama Andmentioning
confidence: 99%
“…Because Mbd2 -/-mice show these phenotypes in the absence of additional changes in behavior or monoamine signaling, we conclude that they are not neuronal in origin and that the absence of MBD2 does not significantly impact neuronal functions. These findings are surprising in the context of the other MBD family proteins, which have been linked to brain-related functions in humans and mice [25,26,28,29,32,33].…”
Section: Discussionmentioning
confidence: 88%
“…Genetic studies of MBD proteins in humans and animal models have demonstrated a critical role for this protein family in the brain [22,[25][26][27][28][29]. Mutations in several MBD proteins have been identified in individuals with autism spectrum disorder (ASD), although further work is needed to determine if these mutations are causative [25,26].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Rare variants in CHD7 are thought to confer increased autism risk, even in the absence of a CHARGE syndrome diagnosis [89]. Further still, mutations in genes highly related to MECP2, such as MBD5, have been found in idiopathic autism [90].…”
Section: Tuberous Sclerosis Complexmentioning
confidence: 99%